2D Reactive Transport Simulations of CO2 Streams Containing Impurities in a Saline Aquifer, Heletz, Israel. (July 2017) - Wolf, J.L.; Niemi, A.; Bensabat, J.; May, F.; Rütters, H.; Rebscher, D.
Abstract: In order to evaluate the chemical impacts of CO2 stream impurities on reservoir rocks, 2D reactive transport simulations using the code TOUGHREACT V3.0 were performed. The underlying reservoir properties are based on in-situ data from the CO2 injection test site Heletz, Israel. Two different CO2 compositions (mole fractions 99% CO2 + 1% SO2 and 98.8% CO2 + 1% SO2 + 0.2% NO2, respectively) were chosen to represent oxidising impurities. Different modelling approaches, namely trace gas transport (TGT) and additional brine injection (ABI), were applied to investigate the influence of these modelling approaches on qualitative and quantitative simulation results. The simulations using either approach show an accumulation of SO2 and NO2 close to the injection well due to the preferential dissolution of these acidic impurities compared to CO2 . Both modelling approaches indicate the same general chemical impact and related mineral reactions. Within the affected rock volume a distinct ankerite to anhydrite conversion occurs, which slightly enhances porosity. While the same qualitative conclusions independently from the chosen modelling approach were obtained, the quantitative magnitude of mineral conversion and the spatial extent of impurity affected rock material depend on the chosen modelling approach and thus need further investigation with respect to e.g. validation by field test data.